Sociocultural practices, beliefs, and myths surrounding newborn cord care in Bayelsa State, Nigeria: A qualitative study. - Chika O Duru; Abisoye S Oyeyemi; Adedotun D Adesina; Ijeoma Nduka; Charles Tobin-West; Alice Nte (Public Library of Science (PLoS), 2023)
Persisting sociocultural beliefs have continued to significantly influence the adoption of recommended newborn care practices by women in Sub-Saharan Africa. This study aimed at identifying the sociocultural practices, beliefs, and myths surrounding newborn cord care by women residing in Bayelsa State, Nigeria. This was a qualitative study that involved 24 women and 3 traditional birth attendants (TBAs) in three focus group discussions and three in-depth interviews respectively. Interview guides were used to lead the discussions and the interviews which were audiotaped, translated and then transcribed. Thematic analysis was done using NVivo QSR version 12.2 Pro. Several themes describing various sociocultural practices, beliefs, and myths surrounding cord care were uncovered. Most women preferred to be delivered by a TBA who usually cuts the infant's cord with a razor blade and ties the stump with hair or sewing thread. Substances used for cord care included methylated spirirt, "African never-die" leaf, and "Close-Up" toothpaste. All the participants agreed that methylated spirit was a potent antiseptic for cord care but none of them had heard about nor used chlorhexidine gel. It was a common belief that abdominal massage and the application of substances to the cord were solutions to common cord-related problems. Mothers, TBAs and relatives were influential regarding choices of cord care practices. Sociocultural practices, beliefs, and myths are still major barriers to the adoption of recommended cord care practices by women in Bayelsa State. Interventions should be targeted at improving delivery in health facilities and educating women in the community on good cord care practices.